Folle d’amour, folle de Dieu : la femme de Potiphar au prisme des cultures .......... 115 - Gorecka-Kalita, Joanna (Pensées orientale et occidentale : influences et complémentarité II, 2021)
FOOL FOR LOVE, FOOL FOR GOD: POTIPHAR’S WIFE THROUGH THE PRISM OF CULTURESThe paper analyses the character of Potiphar’s wife in the intercultural/ interreligious context. The founding story, that of the Book of Genesis, is the starting point; then comes the Hellenistic one (Joseph and Aseneth), the Christian (Morales on Job by Gregory the Great, Moralized Bibles etc.), the Jewish (Testament of the Twelve Patriarchs, the Midrashim etc.) and the Muslim (the Quran, the Tafsir, the Stories of the Prophets etc.) stories and commentaries are presented. Particular attention is given to the Persian texts of the Middle Ages, since they fundamentally reinterpret the character of the heroine: from a lustful and perfidious woman, she becomes the image of a suffering lovestruck virgin and finally an allegory of the soul seeking God in Youssouf and Zouleïkha, Djami’s famous Sufi novel, tinged with Platonism.